Wide Spread Low Grade Endometrial Stromal Sarcoma - Usman, Anum; Lakhnana, Noor Khan; Zafar, Humaira (International Journal of Pathology, 2018)
Endometrial stromal sarcoma is an unusual malignant neoplasm of the uterus. It mainly occurs in the age of 40–50 years. It accounts 2 to 6% of uterine malignancies. Usually, the diagnosis is confirmed postoperatively. Common symptoms are abnormal vaginal bleeding, abdominal mass and mild abdominal pain. We report a case of endometrial stromal sarcoma in a 40 years old woman. Biopsy specimens were received at the pathology lab of ANMCH. She presented with abnormal vaginal bleeding since 4 months. Histopathological findings confirmed the diagnosis of endometrial stromal sarcoma which was then confirmed on immunohistochemistry. We aimed to present a case of endometrial stromal sarcoma because of its rare occurrence and problems in establishing histopathological diagnosis